Curing Effects on High-Strength Concrete Properties - Afaf M. O. Wedatalla; Yanmin Jia; Abubaker A. M. Ahmed (Advances in Civil Engineering)
This study was conducted to investigate the impact of hot and dry environments under different curing conditions on the properties of high-strength concrete. The concrete samples were prepared at a room temperature of 20°C and cured under different curing conditions. Some specimens underwent standard curing from 24 h after casting until the day of testing. Some specimens underwent steam curing in a dry oven at 30°C and 50°C after casting until the day of testing. Other specimens were cured for 3, 7, 21, and 28 days in water and then placed in a dry oven at 30°C and 50°C and tested at the age of 28 days, except for the specimens that were cured for 28 days, which were tested at the age of 31 days, to study the effect of curing period on the strength of concrete exposed to dry and hot environments after moist curing. The effects of hot and dry environments on high-strength concrete with different water/binder ratios (0.30, 0.35, and 0.40), using (30%) fly ash for all mixes, and (0%, 5%, and 10%) silica fume with the binder (450, 480, and 520 kg), respectively, were separately investigated, and the effects of curing under different conditions were evaluated by measuring the compressive strength, flexural strength, microhardness, and chloride diffusion and by assessing the concretes’ microstructure. The relationships between these properties were presented. A good agreement was noted between the concrete compressive strength and concrete properties at different temperatures, curing periods, and curing methods.